(untitled) (International Journal of Mathematics and Physics, 2017)
This paper considers numerical modeling of cloud formation under the action of buoyancy force, taking into account the turbulent mixing and the adiabatic expansion. Based on the solution of the three-dimensional filtered non-stationary Navier-Stokes equation, the continuity equation, the concentration equation, the enthalpy equation, and the equation of state for compressible media numerical modeling of cloud formation is carried out. The modified solver is based on the library Open Foam of solution of mathematical physics problems. To close the basic equations the viscosity model of turbulence is used. Numerical modeling of the formation of clouds formed at ground explosion of the launch vehicle "Proton-M" 2nd July 2013, shows the dependence of the fireball height from the thermodynamic parameters in the atmosphere. Comparison of the cloud rise height as a function of the explosion power with the analytic formula of Satton confirmed the applicability of the mathematical model used to the cloud formation problem in a surface explosion of a launch vehicle. The explosion power is calculated from the funnel size. G M T Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть